Enfranchisement and budget deficits: A theoretical note - Signe Krogstrup; Sébastien Wälti (Graduate Institute of International and Development Studies, 2009)
If women make different economic decisions than men on average, then an increase in women's influence in the political and economic spheres of society might change economic outcomes. In this note, we focus on the impact of female enfranchisement on fiscal policy outcomes. We present a simple median voter model and show that if women have different economic preferences than men, then female enfranchisement leads to a change in government budget deficits.
Keywords: D78; E62; H62; J16; 330; fiscal policy; budget deficit; enfranchisement; median voter; gender; Haushaltsdefizit; Politische Entscheidung; Frauen; Finanzpolitik; Medianwähler-Modell; Theorie